Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal. (31st August 2016) - Givnish, Thomas J.; Spalink, Daniel; Ames, Mercedes; Lyon, Stephanie P.; Hunter, Steven J.; Zuluaga, Alejandro; Doucette, Alfonso; Caro, Giovanny Giraldo; McDaniel, James; Clements, Mark A.; Arroyo, Mary T. K.; Endara, Lorena; et al.
Abstract: Aim: Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal (LDD) in generating orchid diversity. Location: Global. Methods: Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results: Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma (HPD: 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions: Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.